2022
DOI: 10.1021/jacs.2c05373
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Electrocatalytic Reduction of CO2to Ethane over Nitrogen-Doped Fe2O3

Abstract: Non-copper catalysts are seldom reported to generate C2+ products, and the e cient over these catalysts were low. In this work, we reported an iron-based catalyst centered in nitrogen doped γ-Fe2O3 (xFe2O3-N), which yielded C2H6 as major product in H-cell. At -2.0 V vs Ag/Ag+, the Faradaic e ciency (FE) for ethane reaches 42% with current densities of 32 mA cm−2. This is the rst report about selective CO2 reduction to ethane (C2H6) over iron-based catalyst. Results showed that catalyst possessing FeO1.5-nNn si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 60 publications
2
43
0
Order By: Relevance
“…Notably, the CH 4 product by CO 2 photoreduction was formed by the *CH 3 hydrogenation, , and hence the C 2 H 6 generation was kinetically faster with the direct C–C coupling of *CH 3 during the reaction. Comprehensibly, depending on whether the C 1 species of *CO or the possible *CHO was the underlying factor for the C–C coupling step, the *CH 2 CH 2 species or the C 2 H 4 product could be generated during the reaction. , However, the C 2 H 4 product was undetected in the above tests, predicting that the *CH 2 CH 2 intermediate was uneasily obtained with the formation of the C 2 H 6 product. Additionally, only a trace of C 2 H 6 (Figure c) was detected on using the C 2 H 4 reaction gas (∼253 ppm, C 2 H 4 + Ar), suggesting a difficult reaction via the *CH 2 CH 2 pathway for the C 2 H 6 formation.…”
Section: Resultsmentioning
confidence: 97%
“…Notably, the CH 4 product by CO 2 photoreduction was formed by the *CH 3 hydrogenation, , and hence the C 2 H 6 generation was kinetically faster with the direct C–C coupling of *CH 3 during the reaction. Comprehensibly, depending on whether the C 1 species of *CO or the possible *CHO was the underlying factor for the C–C coupling step, the *CH 2 CH 2 species or the C 2 H 4 product could be generated during the reaction. , However, the C 2 H 4 product was undetected in the above tests, predicting that the *CH 2 CH 2 intermediate was uneasily obtained with the formation of the C 2 H 6 product. Additionally, only a trace of C 2 H 6 (Figure c) was detected on using the C 2 H 4 reaction gas (∼253 ppm, C 2 H 4 + Ar), suggesting a difficult reaction via the *CH 2 CH 2 pathway for the C 2 H 6 formation.…”
Section: Resultsmentioning
confidence: 97%
“…Though the Cu-based electrocatalysts have emerged as promising candidates to boost C 2+ production in CO 2 RR, some noncopper electrocatalysts have also achieved superior selectivity for C 2+ product generation. Very recent investigations indicated that the hexagonal cobalt nanosheets possess excellent selectivity toward ethanal production with FE of 60% at −0.4 V (vs RHE), while the nitrogen-doped γ-Fe 2 O 3 favors the formation of ethane with FE of 42% at −2.0 V (vs Ag/Ag + ) . Inspired by this point, it could be feasible to prepare noncopper MOFs (e.g., cobalt- and iron-based MOFs), as well as their derived materials, as electrocatalysts in boosting the conversion of CO 2 to C 2+ products.…”
Section: Discussionmentioning
confidence: 99%
“…Very recent investigations indicated that the hexagonal cobalt nanosheets possess excellent selectivity toward ethanal production with FE of 60% at −0.4 V (vs RHE), 245 while the nitrogen-doped γ-Fe 2 O 3 favors the formation of ethane with FE of 42% at −2.0 V (vs Ag/Ag + ). 246 Inspired by this point, it could be feasible to prepare noncopper MOFs (e.g., cobalt-and iron-based MOFs), as well as their derived materials, as electrocatalysts in boosting the conversion of CO 2 to C 2+ products. Sixth, apart from MOFs, other similar porous materials, such as COFs and HOFs, also hold great potential of promoting C 2+ production in electrochemical CO 2 RR, although most of the reported COFs and HOFs tend to facilitate the CO or CH 4 production at current stage.…”
Section: ■ Structure Of Mofmentioning
confidence: 99%
“…For instance, an N-doped γ -Fe 2 O 3 core-shell architecture was reported to possess a C 2 H 6 FE of 42% with a current density of 32 mA cm −2 . 27 A FeP nanoarray exhibited a CH 3 CH 2 OH FE of 14.1% and current density of 2 mA cm −2 . 28 A Fe 2 P 2 S 6 nanosheet was also reported with a CH 3 CH 2 OH FE of 23.1% and current density of 0.5 mA cm −2 .…”
Section: Fe-based Functional Porous Frameworkmentioning
confidence: 99%
“…, Cu, Co, Ni, Fe, and Zn), metals with CO selectivity (including Sc, Mn, Y, and Re), and metals with HCOOH selectivity (such as In, Sn, and Bi). 23–30 Among them, the Cu element has been demonstrated to exhibit the greatest potential for the ECO 2 RR, which is capable of generating a series of hydrocarbons, e.g. , HCOOH, CH 4 , CH 3 OH, C 2 H 4 , and CH 3 CH 2 OH.…”
Section: Introductionmentioning
confidence: 99%